Penataan Organisasi Balai Kesehatan Mata Masyarakat Provinsi Sulawesi Utara - Achmad, Herry Wiliam; Kaunang, Markus; Tampi, Johny R. E. (JURNAL ILMIAH SOCIETY, 2015)
Community Eye Health Center of North Sulawesi province as a government agency entrusted to serve and handle the eyes of the public health need to make improvements through organizational restructuring to better direction. As for which is the goal of this research is to explain and analyze the organizational structuring Community Eye Health Center of North Sulawesi Province.In this study researchers used a qualitative research design, the purpose of this study can reveal, decipher and understand the structuring organizations exist. The conclusion of this study is the arrangement of organizations in Community Eye Health Center of North Sulawesi province with regard to the availability of resources of employees in terms of quality and quantity, availability and use of technology and culture or employee culture that supports the provision of services have not been going well.Keywords: Structuring the Organization, Employee, Technology, Culture.